Anal sphincter fatigability in assessing anal incontinence: A systematic review. Issue 9 (5th March 2022) - Wickramasinghe, Dakshitha; Wickramasinghe, Nilanka; Kamburugamuwa, Sohan Anjana; Samarasekera, Nandadeva; Warusavitarne, Janindra; Vaizey, Carolynne
Abstract: Background: Diagnosing anal incontinence (AI) based on manometry results is challenging due to the variation of the normal values and overlap between patients with and without AI. This study aimed to perform a systematic review on the difference in sphincter fatigability between patients with and without AI. Methods: MEDLINE, EMBASE, SCOPUS, and Google Scholar were searched. Studies were included if they included adult patients and assessed anal sphincter fatigability between using manometry. The effect size was estimated as the standardized mean difference (SMD) with 95% confidence intervals. A random‐effects model was used. Results: The database searches identified 125 unique articles, and five additional articles were identified from the reference list of articles. One hundred thirteen were excluded through title and abstract review. Nine articles were included in the final analysis. There was no statistically significant difference in the resting pressure between the two groups. Patients with AI had significantly lower squeeze pressure. There was no statistically significant difference between the groups in the fatigue rate. The FRI was significantly lower in patients with AI (SMD 1.636, p  = 0.001). Approximately a third of the patients in one study were able to maintain a contraction for 20s without reducing pressure. There was significant heterogeneity in the studies. The data available were inadequate for more robust calculations. Conclusions: Sphincter fatigability, measured by the Fatigability Rate Index, has good discriminating power for anal incontinence. A standardized protocol needs to be followed by future researchers. Graphical Abstract The analysis used six studies with 413 patients to compare Fatigue Rate Index between patients with AI and controls. All studies reported a lower FRI in patients with incontinence and the FRI was significantly lower in patients with AI (standardized mean difference [SMD] 1.636, p = 0.001). Conflicting results were reported on the correlation between FRI and AI symptom scores. Abstract : The analysis used six studies with 413 patients to compare Fatigue Rate Index between patients with AI and controls. All studies reported a lower FRI in patients with incontinence and the FRI was significantly lower in patients with AI (standardized mean difference [SMD] 1.636, p = 0.001). Conflicting results were reported on the correlation between FRI and AI symptom scores.